TRADING OF AGRICULTURAL PRODUCTS FROM AGROCOMPLEX BETWEEN COUNTRIES FROM BALKAN REGION - Peshevski, Mile; Ameti, Ilaz; Vukaj, Oriola; Petkov, Robert (Economics of Agriculture, 2013)
Republic of Macedonia has solid trade relations with many countries in the world. The most important trade partners for Macedonia, when considering trading volume and value, are member states of EU and countries from Balkan region. Trade value of agrocomplex products is on average 349,3 million EUR – 56% goes to food, 18.5% to beverages and 24% to tobacco. Import value exceeds export value by 117 249 EUR. In view of export value of agrocomplex, most export goes to Serbia and the least to Moldova, but when considering export trade value of vegetables, fruits and tobacco, most export goes to Greece, an the least again in Moldova. In the same time, when considering export value per person for both aforementioned values, first place goes to Kosovo, and last to Romania. The highest import value of agrocomplex products and vegetables, fruits and tobacco in particularly comes from Serbia, and the least from Moldova. In general, Macedonia´s most important trade partner in Balkan region is Serbia, while trading with Moldova is nearly insignificant.